2022
DOI: 10.3389/fphys.2022.1054463
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise-and high fat diet-induced bone marrow extracellular vesicles in stress hematopoiesis

Abstract: Exercise and obesity regulate hematopoiesis, in part through alterations in cellular and soluble components of the bone marrow niche. Extracellular vesicles (EVs) are components of the bone marrow niche that regulate hematopoiesis; however, the role of exercise training or obesity induced EVs in regulating hematopoiesis remains unknown. To address this gap, donor EVs were isolated from control diet-fed, sedentary mice (CON-SED), control diet-fed exercise trained mice (CON-EX), high fat diet-fed, sedentary mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
1
0
1
Order By: Relevance
“…BMSC can differentiate into osteoblasts and adipocytes [43]. Obesity has been shown to facilitate this cell's conversion to an adipocyte, increasing the percentage of adipocytes and decreasing the percentage of osteoblasts in the bone marrow [44,45]. Furthermore, an aberrant buildup of adipocytes in the bone marrow is one of the risk factors for decreased bone turnover and imbalanced osteoblast activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…BMSC can differentiate into osteoblasts and adipocytes [43]. Obesity has been shown to facilitate this cell's conversion to an adipocyte, increasing the percentage of adipocytes and decreasing the percentage of osteoblasts in the bone marrow [44,45]. Furthermore, an aberrant buildup of adipocytes in the bone marrow is one of the risk factors for decreased bone turnover and imbalanced osteoblast activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, research has indicated that obesity augments the population of adipocytes within the bone marrow while concurrently modifying their metabolic function. The bone marrow houses bone mesenchymal stem cells (BMSCs), which possess the capacity to differentiate into both osteoblasts and adipocytes ( 48 , 49 ). The presence of obesity has been demonstrated to promote the differentiation of BMSCs towards adipocytes, culminating in a heightened presence of adipocytes within the bone marrow and a concomitant reduction in the osteoblast population ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos em modelo animal mostram que o tratamento de ratos diabéticos com EVs da circulação de camundongos exercitados promove uma melhora na cicatrização de feridas promovendo angiogênese (98), além disso EV liberadas com exercício parecem ter um papel na hematopoiese (99). Estudos in vitro mostram que o tratamento com EVs liberadas com a prática de exercício físico parece ter um papel positivo no processo de envelhecimento e na regeneração muscular (100,101).…”
Section: Vesículas Extracelularesunclassified